Study of technology and standardization of composite medicines with compound ingredients for use in flu and flu-like diseases - Enkhsaikhan, Khuslen; Batchuluun, Bujinlkham; Davjid, Batdorj; Lkhavga, Maral; Boldsaikhan, Munkhzaya; Gantur, Ganchimeg; Atartsetseg, Maralgoo; Ryenchindorj, Lkhaasuren; Luvsan, Khurelbaatar; Tsegmid, Altantuya (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
According to the World Health Organization, seasonal influenza results in approximately one billion cases annually, with 3–5 million severe complications and 290,000–650,000 deaths worldwide. Symptomatic treatments for fever, headache, joint and muscle pain, nasal congestion, and other related symptoms are commonly used. In our country’s pharmaceutical market, traditional medicines, herbal remedies, and generic drugs with expectorant and fever-reducing properties are domestically produced. This study aimed to develop and evaluate the quality of compounded ingredients formulated as tablets for treating influenza and flu-like illnesses. Tablets containing active ingredients were formulated and compressed to a weight of 600 mg (C1) and 640 mg (C2, C3) using a tablet compression machine. Manufacturing defects, such as capping and cracking, were observed in the C3 tablet. The active ingredient content in C1 was found to be insufficient, failing to meet the established quality requirements. In contrast, the C2 tablet met the quality standards for tablet formulations.